Serious games and e-learning standards: Towards an integrated experience - Hendrix, M.; Dunwell, I.; lameras, P.; Arnab, S.; Petridis, P.; Stewart, C.; de Freitas, Sara; Backlund, P.; Liarokapis, F. (Romania Advanced Distributed Learning Partnership Lab, 2013)
Since the emergence of e-Learning-Learning systems, researchers haveexplored methods to increase their efficacy, and support a wider range of pedagogicalapproaches. Similarly, the concept of using Game Based Learning, taken commonly torefer to the use of digital games for education, has also been the subject of a substantialvolume of research into their pedagogical design and impact. The popularisation of GameBased Learning has occurred in parallel with the establishment of E-Learning systems;however, questions remain on both technical and pedagogical levels as to how games caneffectively be integrated into e-Learning systems. Games can differ substantially from othereducational media when used as learning resources, as they may combine high-fidelityaudio and video content and employ experiential, social, or exploratory pedagogies.Observing that games are not commonly designed to be included in E-Learning-Learningsystems, and that most E-Learning-Learning standards at present do not specificallyinclude affordances for Game Based Learning, this paper explores recent advances instandardisation of Game Based Learning descriptions, and their integration withELearning- Learning standards.